PEDAGOGICAL MODERN TEACHING TECHNOLOGY AND METHODOLOGY OF THE ARTISTIC IDEA OF THE PAINTING LANDSCAPE WORK, COLOR, LINE COMPOSITION METHODS (World Bulletin of Social Sciences, 2025)
This article discusses the problems and solutions of the history of fine art, new modern art trends of Uzbekistan, painting and composition of various genres
Keywords: Taiwanese words and expressions; Technology; egoism of color; character